Turkey as a Trade Partner of Bulgaria – Potential and Realities - Vasileva, Gabriela (Economy and Business Yearbook, 2022)
The purpose of this article is to examine the main theoretical concepts and determinants that are embedded in the understanding of international trade, putting them in the context of bilateral trade cooperation between Bulgaria and Turkey. The main statistics are obtained for the period 2005-2019, considering the effect during and as a result of the Covid pandemic. The exchange of goods between the two countries was examined, as well as Turkey’s investor interest in key sectors in Bulgaria, including the potential for realizing the bilateral tourist flow.